ANALISIS STRATEGI PEMASARAN PELAYANAN SKIN MEDICAL CENTER DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Hariyanti, Endri; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background: Service center medical skin is a new service PKU Muhammadiyah Hospital in Yogyakarta, the necessary research to find out the marketing strategy plan that will be used PKU Muhammadiyah Hospital in Yogyakarta. The marketing strategies of medical skin care center that will be researched to see of the marketing mix, consisting of product, price, place, promotion, people, processes and Physical evidence, from the marketing mix in the analysis using the SWOT analysis to determine the right strategy. Method: The study was descriptive qualitative research. The subjects in this study were the Director of Medical Services, Marketing Manager, one Marketing staff, dermatologist and six patients. The instrument used a form of interview guidelines and the type of recorder. Data analysis Used SWOT analysis. Results: (1) Aspects of the product; Products used in cooperation with Ristra because Ristra is a product that has been certified legal, so safe to use MUI emergency. (2) Aspects of the price, price is still relatively cheap because they still get the discount. (3) Aspects of the place; PKU Muhammadiyah Hospital in Yogyakarta strategically located alongside the highway easily accessible by any transportation making it easier for patients to come to the skin medical center. (4) Promotion: Promotion is not maximized, not broad market area just around the DIY. (5) People; trained human resources, good, loyal and work according to the procedure, Consumers who feel happy and satisfied with the services provided at the medical center skin. (6) Physical evidence; facilities and infrastructure such as physical buildings, medical equipment provided by hospital and has been standard. (7) Process: The process of medical skin care center for treatment tailored to the criteria that will be used in patient care, marketing process of the skin as support medical center for promotional material. Conclusion: The PKU Muhammadiyah Hospital in Yogyakarta in cooperation with the product Ristra because. legal and safe to use, its strategic location but the parking lot should be disciplined, the promotion should be more leverage and targets a broader region, based on SWOT analysis the most appropriate strategy used PKU Muhammadiyah Hospital in Yogyakarta is an aggressive strategy because it can be made in reference to using a strategy oriented to growth stage.Keywords: Skin Medical Center Services, Marketing Mix, SWOT analysis, Strategic Marketing